2012
DOI: 10.1002/chem.201103416
|View full text |Cite
|
Sign up to set email alerts
|

Metamagnetism and Single‐Chain Magnetic Behavior in a Homospin One‐Dimensional Iron(II) Coordination Polymer

Abstract: Reaction of FeCl(2)·4H(2)O with KNCSe and pyridine in ethanol leads to the formation of the discrete complex [Fe(NCSe)(2)(pyridine)(4)] (1) in which the Fe(II) cations are coordinated by two N-terminal-bonded selenocyanato anions and four pyridine co-ligands. Thermal treatment of compound 1 enforces the removal of half of the co-ligands leading to the formation of a ligand-deficient (lacking on neutral co-ligands) intermediate of composition [Fe(NCSe)(2)(pyridine)(2)](n) (2) to which we have found no access in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…Magnetic measurements prove that the metamagnetic behavior is still present but in contrast to the thiocyanato analog, slow relaxations of the magnetization are observed below and above the critical field. In this context it is noted that only a few Fe II homospin SCM compounds are reported in literature and that this behavior was www.zaac.wiley-vch.de [174] never observed before in a selenocyanato coordination polymer. [174] Based on these results we investigated similar compounds with the bidentate ligands 4-bpa and 4-bpe.…”
Section: Fe Compoundsmentioning
confidence: 84%
See 1 more Smart Citation
“…Magnetic measurements prove that the metamagnetic behavior is still present but in contrast to the thiocyanato analog, slow relaxations of the magnetization are observed below and above the critical field. In this context it is noted that only a few Fe II homospin SCM compounds are reported in literature and that this behavior was www.zaac.wiley-vch.de [174] never observed before in a selenocyanato coordination polymer. [174] Based on these results we investigated similar compounds with the bidentate ligands 4-bpa and 4-bpe.…”
Section: Fe Compoundsmentioning
confidence: 84%
“…In this context it is noted that only a few Fe II homospin SCM compounds are reported in literature and that this behavior was www.zaac.wiley-vch.de [174] never observed before in a selenocyanato coordination polymer. [174] Based on these results we investigated similar compounds with the bidentate ligands 4-bpa and 4-bpe. [Fe(NCS) 2 (4-bpe)] n is isotypic to its Co II analogue, which means that Fe(NCS) 2 chains are observed that are linked by the bidentate ligands into layers.…”
Section: Fe Compoundsmentioning
confidence: 84%
“…Subsequently Ishida and co-workers reported a series of similar compounds using the same [Co II (hfac) 2 ] complex [64,65]. Other simple complexes can also be efficiently used as Ising centres in SCMs: Näther and co-workers as well as Miyasaka, Clérac and co-workers reported several SCMs made from Co(II) and Fe(II) pyridine complexes [61,[66][67][68], and Liu, Sato, Duan and co-workers reported SCMs made of Co(II) complexes of 4-styrylpyridine and 4,4 -bipyridine [69,70] Source: Reproduced, slightly modified, from Ref. [12] and Ni(II) [71] and subsequently reported a series of SCMs prepared from [Fe II (DMF) 6 ] 2+ and analogues of it ( Fig.…”
Section: Tablementioning
confidence: 98%
“…For ferromagnetic systems, this scenario is well confirmed 9,14,15 and has been exploited for a number of compounds 16,17 , but for antiferromagnetic chains with non-collinear anisotropy axes 11,18 the situation is much less clear. The problem was revealed 11 for the compound of formula [Mn(TPP)O 2 PHPh]·H 2 O considered a textbook example of SCM (TPP = mesotetraphenylporphyrin and PHPh = phenylphosphinate) and referred to as Mn-CAF (canted antiferromagnet).…”
Section: Introductionmentioning
confidence: 88%